The Relationship Between Maternal Employment and Self-Efficacy in Breastfeeding - Heriyanti widyaningsih; Havifah Alfiani; Eny Pujiati; Noor Faidah; Sri Hartini (Poltekkes Kemenkes Banten, 2026)
ABSTRACT Background: Breast milk is the primary source of essential nutrients for infant growth and development, while also functioning as a natural antibody that strengthens the immune system. The World Health Organization (WHO) and UNICEF recommend exclusive breastfeeding for the first six months of life. However, breastfeeding coverage in Indonesia remains below the national target of 80%, with Kaliwungu Subdistrict, Kudus Regency, reporting a low coverage of only 34.9%. One factor influencing breastfeeding behavior is maternal self-efficacy, which refers to a mother’s confidence in her ability to breastfeed. Self-efficacy may be affected by employment status, as working mothers often face challenges such as limited time, insufficient lactation facilities, and lack of workplace support, all of which may reduce confidence in exclusive breastfeeding. Objective: This study aimed to analyze the relationship between maternal employment and self-efficacy in breastfeeding among mothers in Kedungdowo Village, Kaliwungu Subdistrict, Kudus Regency. Methods: This quantitative study employed a cross-sectional design. The sample consisted of 46 breastfeeding mothers with children aged 0–2 years, selected through stratified random sampling based on inclusion and exclusion criteria. Data were collected using the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF). Statistical analysis was performed using the Pearson Chi-Square test with a significance level of α = 0.05. Results: The bivariate analysis showed a p-value of 0.223, which was higher than the significance level (α < 0.05), indicating no significant relationship between maternal employment and breastfeeding self-efficacy. The findings suggest that both formally and informally employed mothers have comparable levels of breastfeeding self-efficacy. Conclusion: Maternal employment is not the sole factor determining self-efficacy in breastfeeding. Other factors such as knowledge, social support, and prior breastfeeding experience may play more significant roles in influencing mothers’ confidence in breastfeeding.